Factorial Structure and Psychometric Validation of Social Media Intelligence Quotient (SMIQ) Scales among Graduates - Nadhrathul Ain Ibrahim; Rosidah Musa (Information Management and Business Review, 2023)
The Social Media Intelligence Quotient (SMIQ)'s underlying factorial structure will be extracted, and validated, and its psychometric properties will be examined in this study. Self-administered questionnaires from the universities that produce the most employable graduates in Malaysia, such as Universiti Malaya, Universiti Kebangsaan Malaysia, and Universiti Teknologi Mara, were utilized by the researcher to gather the data. It involved 352 final-year students from the Faculty of Business Management. To ascertain the factorial structure of the SMIQ, the researcher used the Exploratory Factor Analysis (EFA). Additionally, the confirmatory factorial analysis (CFA) was used to evaluate the psychometric characteristics of each item to confirm and validate it. A structural model was also developed to measure the nomological validity between social media dependency and SMIQ. It revealed that SMIQ is second order with three factorial structure constructs and met the psychometric criteria. Thus, the findings have essential implications for future research directions and the management of social media skills.